Penerapan Doktrin Kerugian (Schadevergoeding) Perjanjian Kerja Sama Pembangunan dan Pengelolaan Lahan Perumahan (Studi Kasus Putusan Nomor 3179 K/Pdt/2021) - Vania Athalia Lumban Tobing; Audrey Rasya Novianto Putri; Naziva Azzahra Rahman Rahman; Belina Sascika Manalu; Zahwa Cantika Putri Rafian (Esensi Hukum, 2025)
Abstract Default of performance in property development partnership agreements frequently results in substantial material losses and prolonged legal disputes, as evidenced in Supreme Court Decision Number 3179 K/Pdt/2021, which ruled on breach of contract arising from the failure to issue land certificates. This study aims to analyze the application of the doctrine of damages (schadevergoeding) in cases of default concerning partnership agreements for residential land development and management, as well as to examine the legal considerations of judges in assessing losses suffered by capital investors. This research adopts a normative juridical approach employing three methods: case study approach, conceptual approach, and statutory approach. Data is analyzed qualitatively using descriptive-analytical techniques to elaborate and examine findings in accordance with the theoretical framework and applicable legal provisions. The research findings demonstrate that the doctrine of damages constitutes a fundamental legal instrument obligating debtors to compensate for both material and immaterial losses based on the principles of restitutio in integrum and pacta sunt servanda. The Supreme Court corrected the decision of the judex facti, which overly emphasized formal aspects, by prioritizing substantive justice in accordance with the provisions of the Civil Code. The application of this doctrine provides legal protection for aggrieved parties and maintains trust in property business relationships in Indonesia. Keywords: Schadevergoeding, Breach of Contract, Cooperation Agreement, Compensation